Pengaruh Pendapatan, Modal Dan Pola Konsumsi Pengunjung Terhadap Kesejahteraan Pelaku UMKM Di Pantai Lon Malang - Yenti Elia Cristina Girsang; Evaliati Amaniyah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Sampang is a district located in East Java Province, more precisely on the island of Madura. Sampang Regency has a lot of natural tourism wealth that is still unknown to the people of Indonesia, one of which is Lon Malang Beach. Sampang people in general already have an open mindset. Therefore, it is very possible to advance the economy of the Sampang district community through micro small and Medium Enterprises at Lon Malang Beach. Because the income and consumption patterns of visitors greatly affect the welfare of micro small and Medium Enterprises actors in Lon Malang Beach who are also Sampang people. The majority of visitors at Lon Malang Beach are young people and new families. Tourism development efforts must also be adjusted to optimize eligibility standardization and preserve tourist attractions in Sampang Regency. The role of the millennial generation is also a supporting factor for developing and raising tourist attractions in Sampang Regency.